High-sensitivity double-parameter sensor based on the fibre-tip Fabry–Pérot interferometer. Issue 6 (26th March 2017) - Ge, Meng; Li, Yan; Han, Yanhua; Xia, Zehua; Guo, Zhongyi; Gao, Jianmin; Qu, Shiliang
Abstract: We have proposed an ultra-compact double polymer-capped Fabry–Pérot interferometer (FPI), which could be used for simultaneously measuring refractive index (RI) and temperature with low cross sensitivity. The designed and fabricated FPIs have double polymer layers which were fabricated by step-curing ultraviolet photoresist (SU-8) and polydimethylsiloxane on the end face of a traditional single-mode fibre. Three samples were fabricated with different Fabry–Pérot cavity lengths. Experimental results show that the double polymer structure has higher temperature and RI sensitivities than single-layer structure. About 689.68 pm/°C (based on the wavelength shift) in the temperature range of 20–75 °C and −147.04 dB/RIU (based on peak intensity measurement) in the RI range of 1.335–1.355 were measured, respectively. Moreover, the compact structure, high temperature sensitivity and low cross-sensitivity of the FPI make it suitable for integration such as biomedical and microfluidic sensor probe.